Comparing Expectations of Social Workers in Norwegian Trauma-Informed Care Institutions: Perspectives from Social Work Leadership and Young Unaccompanied Refugees (Journal of Comparative Social Work, 2025)
Research: Balancing the expectations of social work leadership and minor, unaccompanied refugees is a key part of the social worker’s professional practice, in the context of Norwegian residential care institutions that have trauma-informed care at the centre of their work. Although there is some understanding in international literature about the expectations of social work leadership and the expectations that unaccompanied minors have of social workers, these expectations have typically been considered in isolation. The nature of any dilemma for social workers arising from conflict between these two sets of expectations is not yet fully understood. This study aims to understand these dilemmas, and we explicitly compare the expectations of social workers held by social work leadership with those held by unaccompanied minors, finding similarities, but also disagreements, which may cause tension for social workers in their practice with the minors in the institution.Methodology: In an explorative, qualitative study, semi-structured interviews were conducted with 11 young male Afghan unaccompanied refugees and seven social work leaders in two Norwegian municipalities. A qualitative thematic analysis was followed by a two-stage cross-comparison of the expectations held by social work leaders and unaccompanied minors to identify agreements and disagreements between expectations. These expectations were interpreted through Bath's trauma-informed care pillars, a well-established theoretical model for social work practice in Norway.Findings: Both groups value empathy, respect, support, extra care, trust and a safe environment. However, different expectations about the flexibility of boundaries, and about emotional closeness, create dilemmas for social workers. By understanding the tensions highlighted in this article, leadership will be better equipped to identify and address the conflicting situations that social workers face due to mismatches between the expectations of leadership and those of young refugees. This study bridges the gap between the theoretical social work concept of trauma-informed care and real-world stakeholder expectations, thus supporting social workers’ awareness on potential dilemmas arising from differing stakeholder expectations.